2022
DOI: 10.4049/jimmunol.2200284
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between HLA Class I and TLR4 Mediates P-Selectin Surface Expression and Monocyte Capture to Human Endothelial Cells

Abstract: Donor-specific HLA Abs contribute to Ab-mediated rejection (AMR) by binding to HLA molecules on endothelial cells (ECs) and triggering intracellular signaling, leading to EC activation and leukocyte recruitment. The molecular mechanisms involving donor-specific HLA Ab–mediated EC activation and leukocyte recruitment remain incompletely understood. In this study, we determined whether TLRs act as coreceptors for HLA class I (HLA I) in ECs. We found that human aortic ECs express TLR3, TLR4, TLR6, and TLR10, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Monocyte recruitment may occur in the early phases of CAV as we observed significantly higher protein expression of CD14 and classical monocytes counts in arteries with low neointima. HLA DSA can rapidly increase intracellular calcium and endothelial presentation of P-selectin, which supports monocyte binding 7,49 . Notably, CD68 protein expression also significantly correlated with coexpressing module ME206 in AOIs with high neointima.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Monocyte recruitment may occur in the early phases of CAV as we observed significantly higher protein expression of CD14 and classical monocytes counts in arteries with low neointima. HLA DSA can rapidly increase intracellular calcium and endothelial presentation of P-selectin, which supports monocyte binding 7,49 . Notably, CD68 protein expression also significantly correlated with coexpressing module ME206 in AOIs with high neointima.…”
Section: Discussionmentioning
confidence: 84%
“…Episodes of antibody-mediated rejection (AMR) in which donor specific antibodies (DSA) target human leukocyte antigens (HLA) present on vascular endothelial cells (ECs) have been increasingly recognized as a major risk factor contributing to CAV 3 . Specifically, DSA can activate EC intracellular signaling cascades inducing EC proliferation, migration, and increased surface expression of adhesion molecules promoting monocyte and NK cell recruitment [4][5][6][7][8] . Moreover, DSA can directly mediate EC-injury by triggering activation of the classical complement cascade 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Through Western analysis, it was observed that ITGB4 expression was increased in NPR1 -kncokdown HUVECs ( Figure 3 E). Furthermore, ITGB4 binds to HLA class I (HLAI) as a complex that strengthens monocyte adhesion via ICAM-1 clustering on endothelial cells by the mTOR signaling pathway [ 27 ]. All of the data suggest that NPR1 deficiency promotes the ITGB4 expression level.…”
Section: Resultsmentioning
confidence: 99%
“…A mouse model of ITGB4 with deletion of cytoplasmic signaling domain reduces the endothelial inflammatory response induced by mechanical stress [ 48 ], while mice with atherosclerotic plaques display an increased ITGB4 [ 9 ]. Recently, a study found that the HLA I/ITGB4 complex stabilizes monocyte adhesion via ICAM-1 aggregation on endothelial cells in an mTOR-dependent manner [ 27 ]. This evidence indicates that ITGB4 participates in endothelial cell adhesion, inflammation, and atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HLA antibodies crosslinking of HLA molecules on endothelial cells stimulates intracellular signaling, including FAK/Src, ERK, PIK, and mTORC1. HLA molecules trigger these signaling pathways by physically associating with integrin β4 or TLR4, thereby leading to activation of endothelial cells and recruitment of leukocytes, which manifests as transplant vasculopathy ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%